An unusual presentation of pancreatic pseudocyst mimicking cystic neoplasm of the pancreas: a case report - Gintowt, Aleksandra (BioMed Central, 2009)
In spite of their rarity, cystic neoplasms of the pancreas are characterized by existing or potential malignancy that cannot be ignored during decisive process with regard to the choice of treatment. Diagnostic difficulties in the differentiation of pancreatic pseudocyst and cystic pancreatic neoplasm can lead to misdiagnosis and inappropriate treatment, since clinical symptoms, preoperative imaging tests and even endoscopic retrograde cholangiopancreatography are often not sufficient to establish the correct diagnosis. We present a case of pancreatic cyst with no typical features of pseudocyst in the medical interview, treated by Child's subtotal pancreatectomy by reason of the high risk of neoplasia suggested by radiological and endoscopic examinations.